Remembering Things We’ve Never Done: Memory’s Daughters and the Literary Experience - William C. Johnson (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Memory, essential in creative writing, inspires us to weave literary reading into the narrative of personal experience and to seek, through recollection, our psychic wholeness.
Keywords: Literary Experience; Remembering; Memory; Mnemosyne; Psyche